THE INTER-RELATIONSHIP BETWEEN TEACHERS OF PHYSICAL EDUCATION, GUIDING AND SUPERVISION RES EDUCATION FOR PRACTICE EDUCATIONALESTABLISHMENT IN ELEMENTARY EDUCATION IN THE CITY OF OLD HARBOR-RO (Fiep Bulletin - online, 2020)
INTRODUCTION: Planet Earth. XXI century. Year 2019. The world population exceeds 7.7 billion people. Of these, almost 800,000 suicides occur per year, according to data from WHO - World Health Organization, the cause of more than half of these cases is depression. Depression is a silent disease with multifactor causes not yet fully known, affecting more than half of the planet's population. It was classified as the disease of the century, because it is a silent disease and still the target of many prejudices, often its treatments are palliative and inefficient. Therapeutic Massage is a complementary treatment to health, acting mainly on the symptoms of the disease and not on the cure of a disorder. OBJECTIVE: The aim of this paper is to investigate the effects of massage therapy on the symptoms of depression. METHOD: This research was conducted using the qualitative descriptive analysis model, through searches in specialized search tools, Pubmed, Lilacs, Google Scholar, Bireme and Scielo. RESULTS: We searched 70 most recent articles, published between 2015 and 2019, which selected 10 through the words massage and depression. CONCLUSION: We conclude that massage therapy acts in the human organism, both mechanically and reflexively, stimulating neurotransmitters through skin receptors, improving symptoms of depression.